Secure data exchange in Industrial Internet of Things - Sukiasyan, Anna (2022)
The use of the Industrial Internet of Things (IoT) is widespread, working as an enabler to implement large, scalable, reliable, and secure industrial environments. Although existing deployments do not meet security standards and have limited resources for each component which leads to several security breaches, such as trust between components, partner factories, or remote-control. These security failures can lead to critical outcomes, from theft of production information to forced production stoppages, accidents, including physical and others. The combination of blockchain-based solutions with IIoT environments is gaining momentum due to their resilience and security properties. However, chain-structured classic blockchain solutions are very resource-intensive and are not suitable for power-constrained IoT devices. To mitigate the mentioned security concerns, a secure architecture is proposed using a structured asynchronous blockchain DAG (Directed Acyclic Graph) that simultaneously provides security and transaction efficiency for the solution. The solution was modelled with special details in the use cases and sequence diagrams. Security concerns were integrated from the start, and a threat model was created using the STRIDE approach to test the security of the proposed solution. As a result, a flexible solution was been developed that significantly reduces the attack vectors in IIoT environments. The proposed architecture is versatile and flexible, is supported by an extensive security assessment, which allows it to be deployed in a variety of customizable industrial environments and scenarios, as well as to include future hardware and software extensions.